Economic optima of sulphar fertilizer for soybean (Glycine max) - JOSHI, O P; BILLORE, S D (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1991-92 to study the effect of sulphur levels on growth, yield and quality of 2 rainted varieties of soybean [Glycine max L). Merr.]. The application of sulphur was beneficial only up to 20 kg S/ha and beyond 40 kg S/ha a negative response of sulphur was recorded. Sulphur levels did not alter the oil content of soybean, while a slight increase in protein was observed up to 60 kg S/ha. ’PK 472’ had an edge over ’MACS 58’ soybean in the performance and response. The economic optimum sulphur doses were 10.37 and 21.85 kg S/ha, giving soybean yield 1 415.48 and 1 113.63 kg/ha for ’PK 472’ and ’MACS 58’ respectively. The maximum estimated yield of’PK 472’ was 1 447.92 kg/ha at 26.73 kg S/ha and of’MACS 58’ was 1 120.63 kg/ha at 56.13 kg/S/ha in the prevailing agro-climatic conditions.